MR Imaging in the Management of Supratentorial Intracranial AVMs - Smith, H. J.; Strother, C. M.; Kikuchi, Y.; Duff, T.; Ramirez, L.; Merless, A.; Toutant, S. (American Journal of Neuroradiology, 1988)
The MR images, CT scans, and angiograms of 15 consecutive patients with intracranial, supratentorial arteriovenous malformations (AVMs) were studied retrospectively. The three imaging techniques were evaluated separately to assess their utility in defining the size, characteristics, and location of the AVM nidus, its arterial supply, and venous drainage. The studies were also evaluated for their ability to show associated parenchymal abnormalities, the presence of mass effect, and changes occurring after embolization. MR was superior to both CT and angiography in showing the exact anatomic relationships of the nidus, feeding arteries, and draining veins, as well as in demonstrating the extent of AVM nidus obliteration after embolization. MR was more sensitive than CT in revealing associated parenchymal abnormalities and subacute hemorrhage. Because of flow-related artifacts and low sensitivity in distinguishing calcification from rapid flow and/or hemosiderin, MR seemed to have a low sensitivity for detecting old hemorrhage within an AVM nidus. Angiography is still needed in the planning of either surgical or endovascular treatment of AVMs.